Development of the Grammar Learning Awareness Scale - Taşdemir, Fazilet; Atalay, Elif; Ekinci Çelikpazu, Esra (Frontiers in Education, 2025)
This study was conducted in order to develop a measurement tool to determine the awareness of why students learn grammar in their mother tongue. The sample of the research consists of 900 participants who continue their education at different grade levels in 6 high schools in a province in Turkey. As a result of the analysis, it was confirmed that the sub-factors of the scale were the components of the structure called grammar learning awareness and that they formed the determined structure together. The model-data fit indexes of the scale were found to be higher than the values accepted by the literature. Cronbach's Alpha internal consistency coefficient scale's sub-dimensions were 0.76 for “The Contribution of Grammar to Individual Development”, 0.76 for “The Contribution of Grammar to Language Skills”, 0.76 for “The Contribution of Grammar to Cognitive Functions” and 0.78 for “The Contribution of Grammar to Communication Skills”. The internal consistency coefficient for the entire scale was determined as 0.83. The obtained values provided evidence showing that the Grammar Learning Awareness Scale is a valid and reliable measurement tool. It is thought that the contribution of grammar learning awareness to individual development, language skills, cognitive functions and communication skills can be measured by this scale.